Examination of in Factor V Leiden and Prothrombin II Thrombophilic Mutations in Czech Young Women Using ddPCR-Prevalence and Cost-Benefit Analysis - Riedlova, Petra; Kramna, Dagmar; Ostrizkova, Silvie; Tomaskova, Hana; Jirik, Vitezslav (Healthcare (Basel, Switzerland), 2021)
BACKGROUND: Thrombophilic mutations in genes for factor V Leiden and factor II prothrombin are among the most important risk factors for developing the thromboembolic disease (TED), along with the use of oral contraceptives (OCs) or smoking. AIM: This study aimed to investigate the occurrence of risk factors in young women using droplet digital PCR (ddPCR) and, based on the results of this investigation, to perform a cost-benefit analysis of ddPCR-based screening in young women starting to take OCs compared to the treatment costs of patients who develop preventable TED in the Czech Republic. METHODS: In this cross-sectional study, female university students filled in a questionnaire and provided a blood sample for DNA isolation and ddPCR analysis of both aforementioned genetic risk factors. The results, along with data from literature and web search, were used for cost-benefit analysis valid for the Czech Republic. RESULTS: Out of 148 participants, 30 (20%) were smokers and 49 (33%) took OCs. A mutation was confirmed in 6 women (4.1%) in the factor V gene and in 3 women (2%) in the factor II gene, respectively. A model calculation on a cohort of 50,000 women starting to use contraceptives in the Czech Republic every year showed that at maximum compliance, (i.e., non-use of OC and smoking cessation), screening could prevent 68 cases of TED over the course of the mean period of OC use (5.7 years). Economically, the costs of testing in this cohort (2.25 mil. USD) would be significantly lower than prevented treatment costs (16 mil. USD at maximum compliance); the cost-benefit break-even point would be at 14.1% compliance. CONCLUSION: The cost-benefit analysis based on our results indicates that screening for factor V Leiden and factor II prothrombin in young women before starting to use OCs would, in the conditions of the Czech Republic, likely be highly economically effective.
Keywords: factor II prothrombin; ddPCR; oral contraceptives; factor V Leiden; smoking; thrombophilic mutation